Measures to ensure the safety of healthcare workers treating tuberculosis and reduce the transmission of tuberculosis among them - Kholibekova Rozikhan Husanboy kizi; Nabiev Sherzodbek Nurmuhammad uglu (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This study examines the risk factors in the working conditions of medical workers involved in the treatment of tuberculosis, the issues of maintaining their health and preventing the spread of the disease. The study substantiates the importance of measures such as the use of necessary protective equipment, adherence to infection control protocols, regular medical examinations, and ongoing training in occupational safety, due to the high risk of tuberculosis infection among medical workers. It also emphasizes the need for effective ventilation systems, isolation measures in health care facilities, and immunization of employees in risk groups to reduce the spread of the disease. The abstract highlights the relevance of ensuring the safety of medical workers in the process of combating tuberculosis and the effectiveness of a systematic approach.